Auxin Modulated Initiation of Lateral Roots Is Linked to Pericycle Cell Length in Maize - Alarcón, M. Victoria; Salguero, Julio; Lloret, Pedro G. (Frontiers in Plant Science, 2019)
Auxin is essential in regulating root system architecture as it controls primary root elongation and lateral root formation. It has been reported that exogenous auxin inhibits primary root elongation and promotes the formation of LR; in maize roots this last process is considered to be initiated from four pericycle cells. In this paper, LR formation in Zea mays primary root has been quantatatively evaluated after exogenous auxin treatments by comparing the effect of auxin in two concrete zones elongated before and after auxin application. In both zones we have determined two main variables: the density of LRs per unit of root length (LRD) and the mean cell length for oppossite phloem pericycle cells. Then, the total number of phloem pericycle cells (PPC) per unit of root length was calculated. Considering that each LR primordium comes from four founder cells (FC), the percentage of PPC (%PPC) that behave as FC in a concrete root zone was estimated by dividing the number of pericycle cells by four times the LRD. This index has been utilised to describe LR initiation. In the root zone elongated in presence of auxin, the application of 1-naphthalene acetic acid (NAA) at low concentrations (0.01 µM) inhibited root elongation by reducing cell length, but also increased LRD. However, high NAA (0.1 µM) strongly reduced both cell length and LRD. On the contrary, both low and high NAA stimulated LRD in zones elongated before auxin application. When the percentage of FC in the phloem pericycle has been analysed in zones elongated in presence or absence of NAA, it has been observed that low NAA increased the %PFC, indicating that LR initiation is promoted in new sites, but high NAA concentration drastically reduced this variable in zones developed in presence of auxin. As these zones are composed of short pericyle cells, we propose that pericycle cell length modulates the response to auxin, and that extremely short pericycle cells are practically blocked for LR primordia initiation.